A Comprehensive QbD Study on Bioadhesive Ocular Films for Improved Conjunctivitis Management: Insights from Design Expert Software - Maddileti, Repollu; Chinthaginjala, Haranath (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives The study aimed to develop ocular films containing levofloxacin to treat conjunctivitis. These films were meticulously prepared using a combination of Gelatin, Aloe barbadensis leaves mucilage, and HPMC K4M, by the solvent casting technique, with the primary objective of enhancing the therapeutic efficacy of levofloxacin for this specific eye condition. Materials and Methods A comprehensive evaluation was carried out to ensure the quality and reliability of the films, encompassing parameters such as film thickness, weight variation, content uniformity, percentage moisture loss, and absorption capacity. In addition, in vitro drug release studies were conducted to simulate the eye's conditions and understand the controlled release of the drug. The study also considered the influence of polymer concentrations, on drug release using Design Expert software’s Box Behnken Design. Results Notably, the research revealed that the ocular films followed zero-order kinetics, meaning they released the drug at a constant rate over time. Conclusion Furthermore, the films demonstrated stability under ambient conditions, making them a promising alternative for prolonged drug delivery and improved therapeutic outcomes in conjunctivitis treatment.
Keywords: Biodegradable; Eye; Film; Levofloxacin; Ocular